Chlamydia trachomatis infection among pregnant women: prevalence and prenatal importance - Paul, V K; Singh, M; Gupta, U; Buckshee, K; Bhargava, V L; Takkar, D; Nag, V L; Bhan, M K; Deorari, A K (The National medical journal of India, 1999)
Chlamydia trachomatis infection in pregnant women is suspected to result in low birth-weight and premature infants. We conducted studies to ascertain the prevalence of this infection among pregnant women in our setting and whether its presence is a risk factor for low birth-weight or prematurity. In the first study, 94 pregnant women between 26 and 30 weeks of gestation were screened for infection with Chlamydia trachomatis. The second investigated a cohort of 172 pregnant women presenting in spontaneous labour. The infection status was related to perinatal outcome in terms of birth-weight and gestation. In both the studies, Chlamydia trachomatis infection was diagnosed using the Chlamydiazyme test performed on endocervical swabs. The prevalence of Chlamydia trachomatis infection in mid-pregnancy and at labour was 17% (16/94) and 18.6% (32/172), respectively. Women with infection were relatively older than those without it [mean (SD) age: 26.6 (4.5) years v. 24.8 (3.6) years, p = 0.01]. The mean (SD) birth-weight [2869 (611) g v. 2814 (496) g], gestation [38.5 (2.6) weeks v. 38.3 (2.0) weeks], and incidence of low birth-weight [18.7% v. 20.7%] as well as prematurity [9.4% v. 10.7%] were similar among neonates born to women with or without infection. Neonates born to infected mothers experienced purulent conjunctivitis more frequently than those born to non-infected mothers [12.5% v. 2.8%, p = 0.04]. Chlamydia trachomatis is a relatively common infection in pregnant women. However, it was not associated with either low birth-weight or prematurity.